Can social network analysis help to include marginalised young women in structural support programmes in Botswana? A mixed methods study - David Loutfi; Neil Andersson; Susan Law; Jon Salsberg; Jeannie Haggerty; Leagajang Kgakole; Anne Cockcroft (BMC, 2019)
Abstract Background In Botswana, one fifth of the adult population is infected with HIV, with young women most at risk. Structural factors such as poverty, poor education, strong gender inequalities and gender violence render many young women unable to act on choices to protect themselves from HIV. A national trial is testing an intervention to assist young women to access government programs for returning to education, and improving livelihoods. Accessing marginalised young women (aged 16-29 and not in education, employment or training) through door-to-door recruitment has proved inefficient. We investigated social networks of young women to see if an approach based on an understanding of these networks could help with recruitment. Methods This mixed methods study used social network analysis to identify key young women in four communities (using in-degree centrality), and to describe the types of people that marginalised young women (n = 307) turn to for support (using descriptive statistics and then generalized linear mixed models to examine the support networks of sub-groups of participants). In discussion groups (n = 46 participants), the same young women helped explain results from the network analysis. We also tracked the recruitment method for each participant (door to door, peers, or key community informants). Results Although we were not able to identify characteristics of the most central young women in networks, we found that marginalised young women went most often to other women, usually in the same community, and with children, especially if they had children themselves. Rural women were better connected with each other than women in urban areas, though there were isolated young women in all communities. Peer recruitment contributed most in rural areas; door-to-door recruitment contributed most in urban areas. Conclusions Since marginalised young women seek support from others like themselves, outreach programs could use networks of women to identify and engage those who most need help from government structural support programs. Methods that rely on social networks alone may be insufficient, and so a combination of approaches, including, for instance, peers, door-to-door recruitment, and key community informants, should be explored as a strategy for reaching marginalised young women for supportive interventions.